THE EFFECT OF ASSISTIVE TECHNOLOGY ON READING COMPREHENSION IN AUTISM SPECTRUM DISORDER STUDENTS : - Kahveci, Gûl; Kara, Donay Nisa (International Online Journal of Education and Teaching, 2023)
In this study, the effect of technology use on reading comprehension skills of students with moderate ASD was examined. Male students who are attending the first grade and have an intermediate level ASD were determined as participants. All three students are reading by swinging. In the research, one of the single-subject research methods, the multiple-probe design across participants was used. The stories used in the training are written in such a way that they consist of 40-45 words. The story difficulty level is 1. It is determined in accordance with the grade level. The level of initiation in the analysis of the data, the ability to understand reading data in the intervention, generalization and maintenance sessions were collected using the data registration form. The reading comprehension a skill was first examined while preparing the form, based on the correct responses supplied to the reading comprehension questions. The research was conducted out by a special education teacher who graduated from the Department of Special Education. In the application of the multiple-probe design across participants as a research model, firstly, the data were gathered in order to decipher the participants' performance in terms of reading comprehension skills by using the data registration form which was prepared for each student. The data were collected in individual sessions and recorded in the relevant sections. While the baseline level data was taken by the practitioner, the related stories were presented in the form of a pen and paper study and the data were collected. In the intervention, generalization and continuity data, the ipad-mediated application was used. The participant opens the story and reads it himself. The teacher shows the questions about the story on the ipad. The reading comprehension data of the participant were performed through multiple choice questions. Consequently, it was found that all participants exhibited appropriate behaviors in keeping on task and completing tasks during the reading comprehension studies process. It has been determined that students with ASD have higher performance when using iPad only compared to traditional books when more than one experiment is performed. The content is one of the most significant aspects in reading comprehension. In this study, the stories were developed by selecting from among the content preferences of children with ASD. Although popular contents were used for children during the baseline phase like other phases, it was determined that pencil and paper works were not preferred. Furthermore, it was discovered that when students began at the most basic level of reading comprehension, their motivation increased when they could answer the questions, and this situation increased the on-task processes and positively affected the comprehension success.